Impact of individualized treatment on recovery from fatigue and return to work in survivors of advanced-stage Hodgkin’s lymphoma: results from the randomized international GHSG HD18 trial - Ferdinandus, Justin; Müller, H.; Damaschin, C.; Jacob, A. S.; Meißner, Julia; Krasniqi, F.; Mey, U.; Schöndube, D.; Thiemer, J.; Mathas, S.; Zijlstra, J.; Greil, R.; et al. (Annals of oncology, 2024)
Background - Persisting cancer-related fatigue impairs health-related quality of life (HRQoL) and social reintegration in patients with Hodgkin’s lymphoma (HL). The GHSG HD18 trial established treatment de-escalation for advanced-stage HL guided by positron emission tomography after two cycles (PET-2) as new standard. Here, we investigate the impact of treatment de-escalation on long-term HRQoL, time to recovery from fatigue (TTR-F), and time to return to work (TTR-W). - Patients and methods - Patients received European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 (EORTC QLQ-C30) and life situation questionnaires at baseline, interim, end of treatment, and yearly follow-up. TTR-F was defined as time from the end of chemotherapy until the first fatigue score <30. TTR-W was analyzed in previously working or studying patients and measured from the end of treatment until the first documented work or education. We compared duration of treatment on TTR-F and TTR-W using Cox proportional hazards regression adjusted for confounding variables. - Results - HRQoL questionnaires at baseline were available in 1632 (83.9%) of all randomized patients. Overall, higher baseline fatigue and age were significantly associated with longer TTR-F and TTR-W and male sex with shorter TTR-W. Treatment reduction from eight to four chemotherapy cycles led to a significantly shorter TTR-F [hazard ratio (HR) 1.41, P = 0.008] and descriptively shorter TTR-W (HR 1.24, P = 0.084) in PET-2-negative patients. Reduction from six to four cycles led to non-significant but plausible intermediate accelerations. The addition of rituximab caused significantly slower TTR-F (HR 0.70, P = 0.0163) and TTR-W (HR 0.64, P = 0.0017) in PET-2-positive patients. HRQoL at baseline and age were the main determinants of 2-year HRQoL. - Conclusions - Individualized first-line treatment in patients with advanced-stage HL considerably shortens TTR-F and TTR-W in PET-2-negative patients. Our results support the use of response-adapted shortened treatment duration for patients with HL.